Pertanggungjawaban Pidana Debt Collector dalam Penarikan Paksa Kendaraan Bermotor: Integrasi POJK 22/2023, Putusan Mahkamah Konstitusi, dan KUHP Nasional - Maruli Simalango; Puguh Aji Hari Setiawan; G. Nyoman Tio Rae (CV. Denasya Smart Publisher, 2026)
Motor-vehicle repossession by debt collectors in distressed financing lies at the intersection of creditors' rights, consumer protection, security law, and criminal law. This study examines the legal limits of debt collection and fiduciary execution and formulates a criminal-liability framework following the enactment of Financial Services Authority Regulation Number 22 of 2023 and Indonesia's national Criminal Code. It employs normative legal research using statutory, conceptual, and case approaches. Legal materials are analyzed qualitatively and prescriptively through normative synchronization and offence-element testing. The study finds that a financing company's mandate does not authorize a debt collector to use threats, violence, pressure, or unilateral seizure. Execution is lawful only where the fiduciary security is registered, default is demonstrable, prior warning has been issued, and the debtor voluntarily surrenders the asset; where default or surrender is disputed, judicial procedure is mandatory. Conduct exceeding these limits may constitute coercion, theft, robbery, extortion, blackmail, or property damage under the Criminal Code, depending on the facts. Financial Services Providers remain responsible for the consequences of outsourcing collection and may incur corporate criminal liability when the attribution requirements under the Criminal Code are satisfied. The study contributes a dual-track accountability model combining the collector's individual criminal liability with the provider's administrative, civil, and corporate responsibility.